2010
DOI: 10.1177/0956797610383434
|View full text |Cite
|
Sign up to set email alerts
|

Abstract Structural Representations of Goal-Directed Behavior

Abstract: Linguistic theory holds that the structure of a sentence can be described in abstract syntactic terms, independent of the specific words the sentence contains. Nonlinguistic behavior, including goal-directed action, is also theorized to have an underlying structural, or "syntactic," organization. We propose that purposive action sequences are represented cognitively in terms of a means-ends parse, which is a formal specification of how actions fit together to accomplish desired outcomes. To test this theory, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Scheepers et al, 2011) and action description (cfr. Allen et al, 2010) significantly influenced the preferred attachment choice in relative clause completion. Furthermore, these within-domain and cross-domain attachment priming effects were similar for all priming conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Scheepers et al, 2011) and action description (cfr. Allen et al, 2010) significantly influenced the preferred attachment choice in relative clause completion. Furthermore, these within-domain and cross-domain attachment priming effects were similar for all priming conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the attachment structures of means end action descriptions can prime each other and are thus abstractly represented (cfr. Allen et al, 2010). We will refer to sentences with means-end parsing in action description as means-end sentences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of syntax was further applied also to human actions in studies exploring the cognitive processes (Allen, Ibara, Seymour, Cordova and Botvinick, 2010;Greenfield, 1991) and their neural correlates (Farag, Troiani, Bonner, Powers, Avants, Gee and Grossman, 2010;van Schie, Toni and Bekkering, 2006). Allen et al (2010) demonstrated that purposive action sequences are processed in terms of a means-ends parse, which is a formal/abstract specification of how actions are linked together in achieving a goal. Means-ends parses may relate to the syntactic frames that bear the abstract structure of a sequence.…”
Section: Communalities Between Language Music and Actionmentioning
confidence: 98%
“…Its effects are evident in recall from long term memory, in which people have a tendency to recall elements in the serial order in which they have frequently occurred in past experience (Miller and Selfridge, 1950). There is also increasing evidence for structured non-linguistic stimuli such as action sequences affecting subsequent production of certain sentence structures, suggesting that the re-use phenomena are not inherently linguistic (Allen et al, 2010; Kaiser, 2012). More broadly, similar Plan Reuse appears in many non-linguistic motor behaviors in humans and animals and is attributed to implicit motor learning.…”
Section: The First Step In the Pdc: Production Difficulty And Its Amementioning
confidence: 99%